Komunikasi Antarpribadi Remaja Lapas Dengan Pendamping(Studi Deskriptif Kualitatif Komunikasi Antarpribadi Remaja di Lapas Klaten dengan pendamping Yayasan Sahabat Kapas Mencapai Keterbukaan Diri) - Chotimah, Khusnul, Palupi, M.A, Rinasari Kusuma, M.I.Kom (2016)
Khusnul Chotimah, L100100126, Communication Interpersonal Youth prisons with Companion (Descriptive Study Qualitative Communication Interpersonal Youth in prisons Klaten Companion Yayasan Sahabat Cotton towards openness Yourself), Thesis, Communication Studies, study program of Communication Studies, Faculty of Communication and Informatics, University of Muhammadiyah Surakarta, 2016. Adolescence is a time of transition in human life, which is common in this age adolescents meet the demands and expectations as well as the dangers and temptations that more kompeks. Teens against the law to have a low level of confidence to be open with others that tend to withdraw from society. Hence the need for interpersonal communication is needed to establish adolescent mental health. Subjects in this study consists of three juvenile prisons and four companion Yayasan Sahabat Cotton. This study aims to determine the stages of the relationship between adolescents with interpersonal communication and self-disclosure companion adolescents in counseling. This study used descriptive qualitative method. Where researchers describe the data obtained in the field. The conclusions obtained in this study is the first stage of interpersonal communication relationship established through three stages, namely, contacts and introductions (contact), keteribatan (involvement), and familiarity (intimacy). In addition to barriers in interpersonal communication, ie internal and external obstacles. Second, the level of self-disclosure (self-disclosure) high teens tend to be seen from the depth of the information disclosed to chaperone juvenile.